2022
DOI: 10.1007/978-3-031-22318-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorandom (Function-Like) Quantum State Generators: New Definitions and Applications

Abstract: Common random string model is a popular model in classical cryptography. We study a quantum analogue of this model called the common Haar state (CHS) model. In this model, every party participating in the cryptographic system receives many copies of one or more i.i.d Haar random states.We study feasibility and limitations of cryptographic primitives in this model and its variants:• We present a construction of pseudorandom function-like states with security against computationally unbounded adversaries, as lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Concretely, we explore two applications: statistically binding and computationally hiding commitments, and pseudo one-time pads. While [AGQY22] previously demonstrated that these applications can be based on logarithmic PRS, we provide alternate proofs assuming the existence of QPRGs combined with Theorem 1.1. Moreover, our constructions resemble the textbook constructions of classical commitments and pseudo one-time pads and thus, are conceptually simpler than the ones presented by [AGQY22].…”
Section: Our Resultsmentioning
confidence: 99%
“…Concretely, we explore two applications: statistically binding and computationally hiding commitments, and pseudo one-time pads. While [AGQY22] previously demonstrated that these applications can be based on logarithmic PRS, we provide alternate proofs assuming the existence of QPRGs combined with Theorem 1.1. Moreover, our constructions resemble the textbook constructions of classical commitments and pseudo one-time pads and thus, are conceptually simpler than the ones presented by [AGQY22].…”
Section: Our Resultsmentioning
confidence: 99%
“…2. If 𝒬 𝑛,𝑞,𝜆 consists of all possible 𝑞 computational basis states then this notion implies a pseudorandom function-like state generator (PRFSG) [AQY22,AGQY22].…”
Section: Our Resultsmentioning
confidence: 99%
“…The notion of pseudorandom states were first introduced by Ananth, Qian and Yuen in [AQY21]. A stronger definition where the adversary is allowed to make superposition queries to the challenge oracles was introduced in the follow-up work [AGQY23]. We reproduce their definition here:…”
Section: Pseudorandom Function-like State (Prfs) Generatorsmentioning
confidence: 99%